2018
DOI: 10.1089/omi.2018.0053
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus: Integrative Analysis of Multiomics Data for Biomarker Discovery

Abstract: Increased fasting plasma glucose (FPG) is an independent risk factor for type 2 diabetes mellitus (T2DM). The development of systems biology technologies for integration of multiomics data is crucial for predicting increased FPG levels. In this case-control study, immunoglobulin (Ig) G glycosylation profiling and genome-wide association analyses were performed on 511 participants, and among them 76 had increased FPG (aged 47.6 ± 6.14 years), and 435 had decreased or fluctuant FPG (aged 47.9 ± 6.08 years). We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…T2DM is characterized as a proinflammatory disease by altered levels of inflammatory biomarkers, including specific cytokines and chemokines (Donath and Shoelson, 2011). Recently, IgG N-glycans have been identified as correlated with T2DM and its risk factors in Asian (Ge et al, 2018) and European (Lemmers et al, 2017) populations. However, these two independent studies displayed the diversities of IgG N-glycomes in T2DM among different populations and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is characterized as a proinflammatory disease by altered levels of inflammatory biomarkers, including specific cytokines and chemokines (Donath and Shoelson, 2011). Recently, IgG N-glycans have been identified as correlated with T2DM and its risk factors in Asian (Ge et al, 2018) and European (Lemmers et al, 2017) populations. However, these two independent studies displayed the diversities of IgG N-glycomes in T2DM among different populations and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Previous glycomics research has shown that IgG Nglycans are associated with the cardiometabolic risk factors, including hypertension (Gao et al, 2017;Liu et al, 2018c;Wang et al, 2016b), T2DM (Ge et al, 2018;Lemmers et al, 2017), central obesity (Russell et al, 2018), and dyslipidemia (Liu et al, 2018a). In this study, we described the association of IgG N-glycans with the 15 cardiometabolic risk factors in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, total plasma N-glycans have been shown to be associated with risk factors of metabolic syndrome (Lu et al, 2011;McLachlan et al, 2016). The inflammatory role of IgG N-glycans, together with their association with the cardiometabolic risk factors, such as aging , central obesity (Russell et al, 2018), dyslipidemia (Liu et al, 2018a), and hyperglycemia (Ge et al, 2018), leads to the hypothesis of this study that the changes to IgG N-glycan profiles are involved in the pathogenesis of cardiometabolic disease by regulating the inflammatory response.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The integration of glycomics with other system science biomarkers might offer further hope for future innovation in diagnosis and treatment of T2DM (Ge et al, 2018), a disease with broad public health importance worldwide. Finally, it is noteworthy that ''Population Glycomics'' is an emerging approach to biomarker discovery for common complex diseases.…”
Section: Discussionmentioning
confidence: 99%